A procedure to estimate cutoff wall transport properties from monitoring wells. (2nd March 2021) - Guida, Giulia; Musso, Guido; Sanetti, Gianluigi; di Prisco, Claudio; Della Vecchia, Gabriele
Abstract: Owing to their capability in limiting the transport of pollutants in the subsoil, cutoff walls are popular solutions for the confinement of contaminants. These barriers are often made of soil‐bentonite or cement‐bentonite mixtures, which are characterized by low hydraulic conductivity, low hydrodynamic dispersion, and long‐term durability. However, the aggressive chemical environment to which these walls are subjected might negatively impact on their performance. Assessment of their performance with time is thus a crucial issue in wall design. The use of dedicated monitoring wells, cast in place inside the wall during construction when the bentonitic mixture is still fluid, can be particularly suitable for both intercepting and detecting the fluids flowing through the barrier. In this research, the results of a numerical study aimed at providing a methodology to estimate the transport properties of the backfill material at the site scale are presented. The methodology relies on abaci and only requires (i) flow and concentration of contaminant data within a monitoring well inside the barrier and (ii) hydraulic head at inlet and outlet of the barrier to be known.